Comparative effect of intraurethral clobetasol and tacrolimus in lichen sclerosus-associated urethral stricture disease - Sunirmal Choudhury; Eeshansh Khare; Dilip Kumar Pal (Urology Annals, 2023)
Background: Management of urethral stricture related to lichen sclerosus (LS) is now gradually changing from surgical to nonsurgical due to availability of anti-inflammatory agents such as corticosteroids and calcineurin inhibitors. We determined the clinical impact of these agents in such patients on outpatient department basis in terms of improvement in symptoms on International Prostate Symptom Score (IPSS), external skin appearance, and maximum urinary flow rate (Qmax). Materials and Methods: Eighty patients of meatal stenosis and penile urethral stricture with histopathologically proven LS were divided into two groups, and clinical and predetermined parameters such as Qmax, IPSS, and changes in external appearance were compared between these groups after 3 months of topical and intraurethral application of clobetasol and tacrolimus with self-calibration. Results: A significant intragroup difference was noted in IPSS (P < 0.001) as well as Qmax (P < 0.001); postintervention intergroup difference in IPSS was not significant (P = 0.94) and however postintervention intergroup difference in Qmax was significant in favor of clobetasol (P = 0.007). A significantly increased number of additional procedures were done in the group receiving intraurethral tacrolimus (P = 0.0473) with significantly less number of skin complication in the group with topically applied clobetasol (P = 0.003). Conclusion: Though both clobetasol and tacrolimus, improved symptom score, Qmax and local external appearance yet topical and intra-urethral clobetasol application via urethral self calibration seems to be better option for lichen sclerosus related urethral stricture in terms cost and local complications.